Strategi Pengelolaan Keuangan Keuangan Rumah Tangga Untuk Mencapai Ketahanan Ekonomi Keluarag - Ratna Dumilah; Ayu Puspa Lestiyadi; Siti Nurcahayati (PT. Karya Inovatif Nusantara, 2025)
The purpose of this community service activity is to provide an understanding of household financial management strategies to achieve family economic resilience for mothers of Posyandu cadres in Jombang Village. The method used in implementing community service activities is material presentation. The technique used in implementing community service activities is brainstorming and discussion with a total of 13 (thirteen) Posyandu cadre mothers whose addresses are at the Posyandu Cadre Forum, Jalan Masjid Al Huda, Kp. Rawa Lele RT 001 RW 017, Jombang Village, Ciputat District, South Tangerang City, Banten 15414. The output of this community service activity is a scientific article published through the Community Service Innovation Journal, as well as increasing the growth and development of creativity, scientific attitudes, professional attitudes, caring attitudes and sensitivity to developments and problems faced related to household financial management strategies, in the Jombang Ciputat Posyandu cadre mothers so that they can achieve economic resilience in the family.